Legal aspects of biological safety in Kazakhstan - Arenova, L.K.; Zhamiyeva, R.M.; Ryabinina, T.K. (Bulletin of the Karaganda University “Law Series”, 2021)
The relevance of the study related to the biological safety of Kazakhstan, which has a legal nature. This is primarily due to the fact that, on the one hand, this direction is a significant element of the national security system, and on the other hand, with ensuring compliance with the legal regime, the stability of public relations, the established state order of rules and norms of behavior. In addition, the legal aspects of biological safety include real and potential risks of committing criminal acts in this area, which can range from the smallest offenses, expressed in non-compliance, disregard of mandatory regimes and compliance requirements for biological safety, to the commission of serious and especially serious crimes, related to sabotage actions, and in general the use of weapons of mass destruction. The main legal aspects of Kazakhstan's biological safety in the period of globalization are considered, and their analysis from the standpoint of preventing criminal acts associated with the use of biological threats, identifying the risks of the emergence and spread of biological threats and their types is conducted. The leading approach to the study of issues related to the legal aspects of biological safety is the system-activity approach and the method of legal analysis of the current national legislation in the area under consideration. The legal aspects of biological safety in the Republic of Kazakhstan at the present stage are presented, a legal analysis of international norms in the field of biological safety is carried out, and their implementation into national legislation, as well as legal proposals on the proposed direction and ways of achieving them, are developed. Considering legal aspects of biological safety as an integral part of the national security system allows solving a number of basic legal problems, which include prevention of the emergence of epidemics and epizootics in natural foci of dangerous infections, massive outbreaks of infectious diseases, including those imported from foreign countries; national control over the level of security of legitimate objects, where various biological agents are stored, moved, transported, manufactured, investigated; identification (monitoring) of the risks of using biological agents for extremist and terrorist purposes due to their availability, prevalence and simplicity.